Journals Need to Adapt Quality Peer-Review Strictly - Bhandari, Ravin; Joshi, Dirgha Raj; Amgain, Kapil (Journal of Karnali Academy of Health Sciences, 2022)
Scientific Publication is obligatory for many reasons, like granting scholarship and for academic promotion. Publication plays vital role in sharing and communicating research findings among scientific communities. Hence, published material should be authentic, free from fraudulence and with accurate conclusion, then only one can carry out further research on the basis of previous findings. Hence, for proper scrutiny and quality control of a study and the manuscript, evaluation and review by experts (peers) of the respective fields is essential.